TRANSPARANSI BIROKRASI PENGADAAN BARANG DAN JASA PUBLIK PADA BIDANG PENDIDIKAN DI KOTA KUPANG (STUDI KASUS PADA DINAS PENDIDIKAN, PEMUDA DAN OLAH RAGA KOTA KUPANG) - Jeferson Tanesab (CV. Multi Kreasi Media, 2022)
This research was motivated by the findings of PIAR-NTT (NGO) where there were at least 135 cases of corruption in the Province of NTT. One of the cases was the process of procuring books at the Office of Youth, Sports and Education of Kupang City in 2012. This study aims at identifying the process of transparency index consisting of some phases such as debating, controlling and disclosure as well as identifying and analysing the factors of guaranteeing the transparency of bureaucracy comprising of cuture, commitmen, programs and processes, integrity of officials and communication channels as well. Thisstudy used a qualitative method and the type of research was a case study. Data collection procedures applied was in-depth interviews and documentary studies. While source triangulation techniques was used for date collection techniques. Meanwhile the subject of research was the PPO Office of Kupang City and determined by a purposive manner. The results showed that the index of transparency did not run well. The reason why the index of transparancydid not run well was because of the weakness of the transparency guarantee.